Fluorescein-Labeled Starch Maleate Nanoparticles as Sensitive Fluorescent Sensing Probes for Metal Ions. (28th January 2014) - Chin, Suk Fun; Azman, Aressa; Pang, Suh Cem; Ng, Sing Muk
Abstract : Fluorescein 5(6)-isothiocyanate starch maleate (FISM) nanoparticles were prepared by covalently attached fluorescein 5(6)-isothiocyanate (FITC) with starch maleate. FISM nanoparticles with a mean particle size of 87 nm were formed via self-assembly upon precipitation in ethanolic solution. FISM nanoparticles were strongly fluorescent with maximum emission wavelength of 518 nm. The fluorescence of FISM nanoparticles can be quenched by silver (Ag + ) and lead (Pb 2+ ) ions in a concentration dependent manner. We have demonstrated the first use of FISM nanoparticles as cheap and effective fluorescent sensing probes for Ag + and Pb 2+ ions with detection limits as low as 2.55 × 10 −5 M and 3.64 × 10 −5 M, respectively.